Analisis Permainan Bahasa dalam Ungkapan “Wacana Penundaan Pemilu Tahun 2024”: Perspektif Ludwig Wittgenstein - Mohammad Fajar Setiawan; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
The discourse of postponing the 2024 election has generated many responses from various groups. In these expressions, of course, using language and the language used in these expressions can cause various responses. Therefore, this study aims to dissect the language context in the expression "discussion of postponing the 2024 election" by using the analytical knife of Wittgenstein's perspective on grammar game theory. The method in this study uses a qualitative approach with library research as the data collection system. The results of this study describe that there is a compatibility between language and the context of language use in the phrase "discussion on postponing the 2024 election". The context includes the language used in this expression, including the political context, because it is uttered by political practitioners and people who have authority in the government and the expression is uttered when Indonesian political parties begin to enter the preparation stage ahead of the 2024 election. Next is the context of the pandemic. COVID-19. In the condition of Indonesia which is being hit by a pandemic, it is very possible to postpone this election, given that there are rules that prohibit crowds. So with this in mind, this expression is an expression that requires meaning and at the same time gives rise to the assumption that this expression can tarnish the face of the constitution in Indonesia.